Broadening our understanding of injury mechanisms to include at-risk situations: an overview of potential injuries at the FIFA men`s World Cup Qatar 2022 - Aiello, F.; Avery, L.; Gardner, T.; Rutherford, H.; McCall, A.; Impellizzeri, F. M.; Peek, K.; Villa, F. D.; Massey, A.; Serner, A. (Science and Medicine in Football, 2024)
This study aims to examine and describe the characteristics of potential injury situations during a men`s professional international tournament quantified using the FIFA Football Language Medical Coding. A prospective study was conducted during the 64 matches of the FIFA World Cup Qatar 2022™, during which five analysts recorded potential injury situations from video analysis. "Potential injuries" were recorded when players stayed down > 5 s and/or requested medical attention. Characteristics were further recorded for variables such as opponent`s action and body location. In total, 720 potential injury situations were recorded of which 139 required medical assessment. The actions which resulted in most potential injuries were running while receiving a pass (74; 10%), while passing the ball (59; 8%), and while progressing with the ball (48; 7%). Duels and ball progression led to a potential injury in 3.0% and 2.1% of all similar actions in total. Both aerial duels and ball progression led to an potential injury that required medical assessment on 0.4% of occasions. Most potential injuries involved the head (149; 21%), foot (120; 17%), or lower leg (110; 15%) with most medical assessments of the head (35; 25%), lower leg (17; 12%), and knee (15; 11%) with a median duration of 47 seconds (IQR 28-61). This study provides a detailed overview of match circumstances that may have a higher injury risk. Although some variables within the coding system need improvement to increase reliability, its use will allow a more detailed comparison of differences between high-risk player actions leading to injury and those that do not, which can improve future prevention strategies.